A novel hybrid battery thermal management system with fins added on and between liquid cooling channels in composite phase change materials. (5th May 2022) - Zhang, Furen; Zhai, Lei; Zhang, Lin; Yi, Mengfei; Du, Bolin; Li, Shiyuan
Highlights: A new way of adding combined fins on and between cooling channels in phase change materials was proposed. The combination mode of internal and external composite phase change materials was optimized. The layout forms of three liquid cooling channels were discussed, and the channel spacing was optimized. Three fin layouts were studied, and the height of each segment fin of the best layout was optimized. Temperature drop and temperature uniformity increased by 27.63% and 35.58%, respectively. Abstract: In order to lighten and simplify the battery pack structure and avoid problems such as poor heat dissipation caused by uneven liquefaction of phase change materials after the introduction of liquid cooling, so as to effectively improve the heat dissipation performance of the battery pack and control its maximum temperature and maximum temperature difference, a new way of adding combined fins on and between cooling channels in phase change materials was proposed in this paper. The reliability of CFD simulation method was proved by the phase change material battery pack experiment. Firstly, the effect of the combination of different phase change materials on the heat dissipation performance of the battery pack was studied. In order to further reduce the temperature of the battery pack, the liquid cooling mode was introduced this paper. Then, designed and discussed the influences of three liquid cooling channel layout modes on the temperature of the battery pack, and optimized the channel number and spacing of the optimal layout mode. The results showed that the introduction of liquid cooling could effectively reduce the maximum temperature of the battery pack, but the maximum temperature difference of the battery pack would increase slightly. In order to enhance the heat dissipation performance of battery pack without energy consumption, a new method of adding fins on liquid cooling channel was proposed. The effects of three fin arrangements on battery pack temperature were designed and analyzed, and the fin height of the optimal arrangement was optimized. It showed that the reasonable arrangement of fins on the liquid cooling channels could reduce the maximum temperature of the battery pack and improve the temperature uniformity of the battery pack. Finally, the influence of coolant flow on battery pack temperature was analyzed. The results demonstrated that with the increase of flow rate, the decreasing trend of the maximum temperature of the battery pack gradually slowed down, while the maximum temperature difference of the battery pack first decreased and then increased. Compared with the Pure paraffin model, when the flow rate was 3.2 g/s, the maximum temperature of the optimal model was reduced by 18.28 °C (27.63%) and the maximum temperature difference was reduced by 0.74 °C (35.58%).